Pengaruh Variasi Ukuran Partikel Marmer Statuari Terhadap Sifat Mekanik Komposit Partikel Marmer Statuari - I Gede Mahayatra; Harnowo Supriadi; Shirley Savetlana (Jurnal Ilmiah Teknik Mesin, 2013)
Abstract Manufacture a composite material with a matrix resin epoxy  and marble statuary powder as filler is one industry-utilization of waste. Mechanical properties of the composite material is influenced by the particle size of the particles. variations in particle size would form different mechanical properties. This research was conducted to investigate the effect variations in particle size on the mechanical properties of the composite particles. In this research variation in particle size marble  statuary  used is 60 mesh, 100 mesh, 140 mesh and 200 mesh. Resin used is epoxy resin, and composition of the volume ratio between the matrix and the particles used in research was 80%: 20%. The method is used in the manufacture of composite hand lay-up method. Tests performed in this research is XRD testing on solid marble, bending strength, hardness, and SEM. XRD results obtained from the testing phase identified in the marble statuary are Ca2O5Si , CaCO3, CaO, SiO2 , MgO , MgCO3 , and SiC. Hardness value of composite particles of marble is 22.3 to 48.33 HB, and flexural strength values of composite particles of marble statuary  is from 13.89 to 38.89 N/mm . Particle size is good for filler in the composite is 140 mesh particles. Marble composite particles 140 mesh particle size has a flexural strength and hardness highest, because SEM photograph composite of 140 mesh particle distribution in the matrix evenly, and there is a good bond between the matrix and particles of marble statuary. Keywords: Marble statuary, composite, particle size marble, epoxy , the mechanical properties